2020
DOI: 10.1111/cpr.12970
|View full text |Cite
|
Sign up to set email alerts
|

Super enhancers—Functional cores under the 3D genome

Abstract: Cell fate is precisely regulated in the developmental process and human disease. Since the discovery of Mendelian, gene regulation models are continuously developing. 1-4 In the beginning, the transcriptional models were linear. 5-8 In the 1980s, the first enhancer was identified which can increase gene expression by 200-fold. 9 With technological development, the study of chromatin is expanded into three dimensions (3D). Distal enhanced elements transmit the activation signal to the promoter by chromosome fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 160 publications
0
16
0
Order By: Relevance
“…Chromatin conformation data offers complementary information and has been found to enhance our capabilities in generating and prioritizing potential functional mechanisms when integrated with alternative approaches (Fulco et al, 2019;Marsha Wheeler et al, 2021;Sun et al, 2022). In addition, DNA 3D organization help us gain insights in the orchestration of different regulatory elements, revealing enhancer-enhancer networks (Beytebiere et al, 2019;di Giammartino et al, 2019), super enhancers that regulate multiple genes (Huang et al, 2018;Zhang et al, 2021), and super interactive promoters (Song et al, 2020;Wen et al, 2022) that tend to have higher extent of enhancer redundancy. We urge future studies to increasingly generate and leverage relevant chromatin 3D organization information, which will significantly facilitate advancing GWAS findings to ultimate clinical transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin conformation data offers complementary information and has been found to enhance our capabilities in generating and prioritizing potential functional mechanisms when integrated with alternative approaches (Fulco et al, 2019;Marsha Wheeler et al, 2021;Sun et al, 2022). In addition, DNA 3D organization help us gain insights in the orchestration of different regulatory elements, revealing enhancer-enhancer networks (Beytebiere et al, 2019;di Giammartino et al, 2019), super enhancers that regulate multiple genes (Huang et al, 2018;Zhang et al, 2021), and super interactive promoters (Song et al, 2020;Wen et al, 2022) that tend to have higher extent of enhancer redundancy. We urge future studies to increasingly generate and leverage relevant chromatin 3D organization information, which will significantly facilitate advancing GWAS findings to ultimate clinical transformation.…”
Section: Discussionmentioning
confidence: 99%
“…A future study using ChIP-mass spectrophotometry may be necessary to accurately determine the molecular interactions in intact super-enhancer complexes [ 30 ]. Recent studies have also reported evidence for the formation of phase-separated condensates—microscopically detectable transcriptional regulatory complexes [ 31 , 32 ]—in super-enhancer regions. An intriguing question is whether such phase-separated condensates can also be found in mammary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above results, the enhancer regions with which Nanog interacts are thought to assemble into an interaction cluster when escaping from the pluripotency state. Since the formation of a super-enhancer causes local chromatin condensations (Zhang et al ., 2021), this interpretation does not contradict the MSD results. Alternatively, the decrease in the number of loci with which Nanog and Oct4 interact along with the euchromatin–heterochromatin transition relatively increases the affinity of the remaining loci to Nanog or Oct4, causing the emergence of interacting clusters.…”
Section: Discussionmentioning
confidence: 99%